e*Singular–Hollow Modules and e*Singular–Coclosed Submodules - Kabban, Ali A.; Khalid , Wasan (Iraqi Journal of Science, 2025)
In this article, we will go over the basics of e*S–hollow modules, e*S–coessential submodules and e*S–coclosed submodules as a generalization of the concepts of hollow modules, coessential submodules and coclosed submodules, respectively. We shall demonstrate some characteristics of these ideas.